Effectiveness of interventions to reduce child marriage and teen pregnancy in sub-Saharan Africa: A systematic review of quantitative evidence - Feyissa, Garumma Tolu; Tolu, Lemi Belay; Soboka, Matiwos; Ezeh, Alex (Frontiers in Reproductive Health, 2023)
Introduction Child marriage and teen pregnancy have negative health, social and development consequences. Highest rates of child marriage occur in sub-Saharan Africa (SSA) and 40% of women in Western and Central Africa got married before the age of 18. This systematic review was aimed to fill a gap in evidence of effectiveness to reduce teen pregnancy and child marriage in SSA. Methods We considered studies conducted in sub-Saharan Africa that reported on the effect of interventions on child marriage and teen pregnancy among adolescent girls for inclusion. We searched major databses and grey literature sources. Results We included 30 articles in this review. We categorized the interventions reported in the review into five general categories: (a) Interventions aimed to build educational assets, (b) Interventions aimed to build life skills and health assets, (c) Wealth building interventions, and (d) Community dialogue. Only few interventions were consistently effective across the studies included in the review. The provision of scholarship and systematically implemented community dialogues are consistently effective across settings. Conclusion Program designers aiming to empower adolescent girls should address environmental factors, including financial barriers and community norms. Future researchers should consider designing rigorous effectiveness and cost effectiveness studies to ensure sustainability. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022327397.